Cell-Free DNA Plasma Levels Differ in Age-Specific Pattern in Healthy Rats and Castrates with Testosterone-Induced Benign Prostatic Hyperplasia. (2nd June 2019) - Vasilyeva, I. N.; Bespalov, V. G.; Von, J. D.; Semenov, A. L.; Tochilnikov, G. V.; Romanov, V. A.; Alvovsky, I. K.; Baranenko, D. A.
Abstract : The purpose of this work was to study changes in the level of cell-free DNA (cfDNA) in the blood of young and old rats in the normal state and with induced benign prostatic hyperplasia (BPH). Male Wistar rats were divided into 4 groups—young (3 months), old (20 months), intact, or with testosterone-induced BPH. Groups with BPH were subjected to surgical castration and administration of testosterone esters at a dose of 25 mg/kg for a total of 7 injections for 20 days. In intact animals, the level of cfDNA in old rats (2.00 ± 0.14 ng/ μ l) was significantly higher than that in the young (1.02 ± 0.30 ng/ μ l). The body and the prostate weights of old rats were 1.6 and 1.4 times larger than those of the young, without an increase in the prostate index (PI). The testosterone level in the blood of young rats was 1.6 times higher than that of old (6.20 ± 0.93 nmol/l vs.3.77 ± 0.55 nmol/l; NS). In animals with BPH, the level of cfDNA in old rats (3.14 ± 0.76 ng/ μ l) was significantly higher than that in young rats (0.80 ± 0.14 ng/ μ l). The body and the prostate weights in old rats were 1.8 and 2.3 times larger, than those in young rats, with an increase in the PI. The level of testosterone in the blood of young (15.76 ± 0.51 nmol/l) and old (16.99 ± 1.1 nmol/l) rats was not significantly different. Morphological signs of BPH were observed in the prostate of both young and old rats. During the induction of BPH in the experiment, according to the level of cfDNA, cell death processes have not changed significantly in young rats but significantly increased in old rats. A similar trend was observed in the group of intact animals. The obtained data indicate that apoptosis processes are enhanced during the development of BPH despite the growth of tissues in the prostate itself.